Peran Manajemen Lingkungan Dalam Pengembangan Pariwisata Berkelanjutan Di Objek Wisata Asstro Highland Ciater (Jurnal Manajemen Pariwisata dan Perhotelan, 2024)
This research aims to examine the role of environmental management in supporting the development of sustainable tourism at Asstro Highland Ciater. Apart from that, this researcher aims to find out and evaluate the concept of environmental management in order to preserve the environment. The background of this writing is because this tourist attraction relies heavily on nature. so environmental management is very important to study, several problems that want to be discussed include: 1. waste management that is not yet optimal 2. increased use of natural resources such as water and energy that is not controlled 3. as well as low awareness of tourists and local communities which has an impact on damage to local ecosystems, the method used includes in-depth interviews with tourist attraction managers and local communities to identify policies and managerial practices implemented in environmental management. Apart from that, field observations were carried out to assess environmental conditions and interactions between visitors and the natural surroundings. The main results obtained from this research were: 1. Efforts to reduce plastic waste 2. Conservation measures which include the use of water-saving equipment and energy use 3. Management can provide education to tourists regarding the importance of maintaining cleanliness and preserving nature, from this research it can recommend the development of ecotourism and strengthening sustainable tourism branding through preserving nature.